2008
DOI: 10.1002/art.23913
|View full text |Cite
|
Sign up to set email alerts
|

Use of nonbiologic disease‐modifying antirheumatic drugs and risk of infection in patients with rheumatoid arthritis

Abstract: Objective. Rheumatoid arthritis (RA) is associated with increased frequency of and mortality from infections, which may be related to host factors, RA itself, inflammation, or medication side effects. This study was undertaken to determine the effect of nonbiologic disease-modifying antirheumatic drugs (DMARDs) on infection risk in RA. Methods. We performed a retrospective, longitudinal study of a population-based RA cohort in British Columbia, Canada, followed from January 1996 to March 2003 using administrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
107
0
3

Year Published

2009
2009
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 159 publications
(122 citation statements)
references
References 39 publications
(54 reference statements)
10
107
0
3
Order By: Relevance
“…In contrast, patients who were prescribed corticosteroids alone (adjusted risk ratio 1.9, 95% CI 1.75-2.05) or with DMARDs (adjusted risk ratio 1.63, 95% CI 1.5-1.77) had significantly increased risk of serious infections. 59 Jenks et al found that an incidence of severe infections associated with a use of leflunomide in RA was 3.30/100 patient-years (95% CI 1.65-5.90). Eleven patients (11/171) developed infection requiring hospitalization, including 3 episodes of lower-respiratory-tract infection.…”
Section: Dmards and Infection Riskmentioning
confidence: 99%
“…In contrast, patients who were prescribed corticosteroids alone (adjusted risk ratio 1.9, 95% CI 1.75-2.05) or with DMARDs (adjusted risk ratio 1.63, 95% CI 1.5-1.77) had significantly increased risk of serious infections. 59 Jenks et al found that an incidence of severe infections associated with a use of leflunomide in RA was 3.30/100 patient-years (95% CI 1.65-5.90). Eleven patients (11/171) developed infection requiring hospitalization, including 3 episodes of lower-respiratory-tract infection.…”
Section: Dmards and Infection Riskmentioning
confidence: 99%
“…To this end the data is conflicting in part due to the inclusion of long term cohorts with severe disease in analyses [32]. In other cohorts, steroids appear to demonstrate a higher risk of infection compared with MTX [33] and several large cohorts have not demonstrated a clear relationship between MTX and increased infection risk [34][35][36].…”
Section: Intercurrent Infection Riskmentioning
confidence: 99%
“…27 Rheumatoid arthritis is itself a risk factor for hospital admission due to infection, and oral steroids and biologics are associated with an increased risk of hospitalisation, as well as an increased risk of mild infections. 28 Cyclophosphamide and azathioprine are also associated with an increased risk of admission with infection. 29 Biologic therapies are associated with more severe infections, particularly pneumonia and soft-tissue infections.…”
Section: New Biologicsmentioning
confidence: 99%